PENEGAKAN HUKUM DALAM PUTUSAN HAKIM UNTUK PERKARA YANG MENIMPA MASYARAKAT KECIL - Paramitha Ariana; Yusuf Setyadi (INTELIGENSIA MEDIA, 2023)
Along with the development of science and technology from time to time of civilization, humans also experienced changes, and then new problems arose, of course, all of which needed more progressive legal rules to provide balance to these social changes. Nowadays there are often legal cases that refer to